Latest progresses in the preparation of tannin-based cellular solids. (January 2015) - Celzard, Alain; Szczurek, Andrzej; Jana, Prasanta; Fierro, Vanessa; Basso, Maria-Cecilia; Bourbigot, Serge; Stauber, Martin; Pizzi, Antonio
Tannins are non toxic, cheap and abundant polyphenolic oligomers extracted from tree barks. They can be easily used for preparing thermoset resins that are natural at the 70–95% level, depending on the cases. From these resins, highly porous monoliths can be obtained by different techniques such as classical physical or chemical foaming, mixed physical/chemical foaming, by less-conventional methods such as emulsion-templating and stabilisation and hardening of either aerated emulsions or liquid foams. The resultant materials are not only interesting per se, but are also key precursors of novel cellular carbons having a broad range of applications. The present paper briefly reviews the latest advances for producing tannin-based cellular materials and their related characteristics and properties.